Effect Of BUMDes on Increasing PADes in Blawi Village, Karangbinangun District, Lamongan Regency - Erna Hayati; Khoirul Bariroh (Institute of Computer Science (IOCS), 2021)
To optimize village assets and the potential to benefit community welfare, the central government encourages the village government to form Village-Owned Enterprises (BUMDes). Blawi Village, which is located in Karangbinangun District, Lamongan Regency, is one of the villages that has owned BUMDes since 2014. If seen from the financial report data, Blawi Village's income from BUMDes has increased. This study aims to determine whether BUMDes has a significant effect on increasing Village Original Income (PADes) in Blawi Village. The data used in this research is the entry data from BUMDes and PADes Blawi Village data from 2015 to 2019. The method used in analyzing the data is linear regression analysis. The results of data analysis show that the income of Desa Blawi from BUMDes has a significant effect on PADes Desa Blawi.